PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP DI KECAMATAN TAMAN PEMALANG - Sri Dewi Agusrina, 11.52.02.0011 (Students Journal of Economic and Management, 2013)
This study was investigated about the role of organizational culture moderated influence headmaster supervision and motivation on teacher performance. Specifically, this study to examine and analisys whether the role of organizational culture moderated influence headmaster supervision and motivation on teacher performance. The contribution of this study is explain and explore the previous research about the influence organizational culture, headmaster supervision, and motivation on teacher performance . Population and study sample was a junior high school teacher Taman District Regency Pemalang as much as 145 people. The research data is the primary data collected directly from the respondents to the questionnaire. The research method approach with computer software SPSS for Windows version 16. The method of data analysis using Moderation Regression analisys (MRA) type quasi moderator. The results showed organizational culture to weaken the effects of headmaster supervision on teacher performance, and the organizational culture does not moderate the effects of motivation on teacher performance. Keywords:Â Â headmaster supervision, motivation, organizational culture, teacher performance